A Critical Review of Urban Sprawl Studies - Chettry V. (My University, 2025)
Rapid and haphazard urban growth has triggered urban sprawl and induced irreversible land cover conversions. In this context, studies are required to comprehensively review the existing urban sprawl research for advancing the knowledge in this domain and determine state-of-the-art development and recent advancements. Multiple definitions of urban sprawl were collected from scholarly sources to determine the commonly accepted understanding of this phenomenon. The analysis encompassed different facets of urban sprawl, including its features and impacts, factors contributing to its occurrence, and factors accelerating its expansion. Furthermore, the approaches to detect and measure urban sprawl were gathered, which included scale, indicators, use of RS and GIS, landscape metrics, entropy indexes, and typologies. This study also attempts to reveal the research gaps. This study identified ambiguity while defining urban sprawl; therefore, no globally accepted definition has been framed until now. Despite the increasing importance of mid-sized cities in achieving sustainable urban development, there is a lack of assessment of urban sprawl in these cities. Limited studies consider urban agglomeration as a unit of investigation for the urban sprawl assessment. There is a requirement for an effective urban sprawl assessment method in developing nations where data availability is a significant constraint. © 2023, The Author(s), under exclusive licence to Springer Nature Switzerland AG.